Seroprevalence of African swine fever in pigs for slaughter in Leyte, Philippines - Portugaliza, Harvie P (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: This study aims to determine the seroprevalence of African swine fever (ASF) in pigs for slaughter in Leyte, Philippines. It underpins the concept that recovered and infected pigs from ASF are likely sent for slaughter to avoid perceived economic losses. Materials and Methods: A cross-sectional study was conducted from March to June 2023 in eight abattoirs, each representing both a city and a municipality in Leyte province. A total of 218 blood samples from 78 farms were examined for ASF virus (ASFV) (VP72) antibodies using a blocking enzyme-linked immunosorbent assay (ELISA) method. Descriptive and seroprevalence analyses were performed. Results: ASF antibodies were detected in pigs for slaughter from abattoirs in Baybay and Ormoc cities, showing a seroprevalence of 3.57% (1/28 pigs) and 2.27% (1/44 pigs), respectively. An apparent absence of ASF antibodies was observed among pigs for slaughter in Isabel, Villaba, Abuyog, Kananga, Dulag, and Macarthur. The farm-level seroprevalence was 2.56% (95% CI: 0.71%–8.88%), while the pig-level seroprevalence was 0.91% (95% CI: 0.25%–3.27%). Conclusion: Detecting ASF antibodies among pigs for slaughter implies exposure to the virus from the farm of origin. This means that, on some farms, ASF remains unreported or undiagnosed. Active surveillance is needed for early case detection and rapid response to control the spread of ASF in the country. Adv. Vet. Anim. Res., 11(1): 65-70, March 2024 http://doi.org/10.5455/javar.2024.k748